Moral Value in Lyrics of Dangdut Compesed by Rhoma Irama - Mustolehudin mustolehudin (Analisa: Journal of Social Science and Religion, 2012)
Moral values undoubtedly play a significant role in human life. These values are not only in religious texts (such as Qur’an, Hadits, Old Testament, Bible, Book of Psalms) but also in literatures. One of the examples is lyrics of Rhoma Irama’s song from 1970s to 1980s. This is a library research using a content analysis approach. Meanwhile, this research utilizes semiotic and hermeneutic methods. The findings show that the lyrics of Rhoma Irama’s song during 1970-1980 contained some moral values which could be implemented in personal life, family, society and religious life. The important values contained in such songs are amanah (trustful), as-siddiq (truth, honesty), al-‘adl (justice), al-rahmah (love), al-ukhuwah (brotherhood) and tasamuh (tolerance). The aforementioned values refer to  two Islamic primary sources that are relevant to all times, in the past, present and future.